Macy's and digital and social media. (AMA-TV., 2014)
In this episode, AMA TV covers amusement parks and job hunt networking. It begins by reviewing research Disneyland conducted when surveys suggested customers might be too happy, and concludes with tips on how to leverage the most out of your personal network connections.